2014
DOI: 10.2147/jbm.s50644
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of hemophilic arthropathy and hematomas

Abstract: Hemophilia is a hematological disorder characterized by a partial or complete deficiency of clotting factor VIII or IX. Its bleeding complications primarily affect the musculoskeletal system. Hemarthrosis is a major hemophilia-related complication, responsible for a particularly debilitating chronic arthropathy, in the long term. In addition to clotting factor concentrates, usually prescribed by the hematologist, managing acute hemarthrosis and chronic arthropathy requires a close collaboration between the ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
142
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 45 publications
(61 reference statements)
0
142
0
13
Order By: Relevance
“…Ключевую проблему гемофилии детского и юношеского возраста представ-ляют рецидивирующие спонтанные гемартрозы. Раннее возник новение синовитов и неизбежное их прогрессиро-вание у больных гемофилической артропатией протекает с поражением периартикулярных тканей, деструкцией хряща, околосуставным остеопорозом и приводит снача-ла к снижению функции сустава, а в дальнейшем к анки-лозу, ранней инвалидизации пациентов и необходимости эндопротезирования суставов [1][2][3].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Ключевую проблему гемофилии детского и юношеского возраста представ-ляют рецидивирующие спонтанные гемартрозы. Раннее возник новение синовитов и неизбежное их прогрессиро-вание у больных гемофилической артропатией протекает с поражением периартикулярных тканей, деструкцией хряща, околосуставным остеопорозом и приводит снача-ла к снижению функции сустава, а в дальнейшем к анки-лозу, ранней инвалидизации пациентов и необходимости эндопротезирования суставов [1][2][3].…”
Section: Introductionunclassified
“…Распространенность ингибитор-ных форм при гемофилии А составляет 11-13% и около 5% при гемофилии В. Наличие ингибиторных антител усугубляет тяжесть клинического течения гемофилии, кровотечения приобретают неконтролируемый характер, а заместительная терапия становится малоэффектив-ной. В связи с этим необходимо регулярное наблюдение за состоянием пораженных суставов для оценки эффек-тивности и, при необходимости, своевременной коррек-ции применяемой терапии [2,[6][7][8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The relative lack of clotting factor determines the severity of hemophilia, with severe cases typically involving factor levels <1% of normal. 21 Treatment of hemophilia involves replacing the deficient factor with recombinant or plasma-derived clotting factor concentrates. 7 Unfortunately, therapy can be complicated by the formation of inhibitors against factor VIII or IX when they are recognized in affected patients as foreign proteins.…”
mentioning
confidence: 99%
“…Approximately 25% to 30% of hemophilia A patients and 3% to 5% of those with hemophilia B will develop inhibitors. 21 Hemarthropathy is a potentially debilitating manifestation of hemophilia that can cause progressive joint destruction. Whereas the pathophysiologic mechanism is not completely understood, it has been suggested that blood is a noxious stimulus that leads to synovial inflammation.…”
mentioning
confidence: 99%